Policy pathways for perennial agriculture - Scott, Emma I.; Toensmeier, Eric; Iutzi, Fred; Rosenberg, Nathan A.; Lovell, Sarah Taylor; Jordan, Nicholas R.; Peters, Tessa E.; Akwii, Esther; Broad Leib, Emily M. (Frontiers in Sustainable Food Systems, 2022)
● Perennial agriculture refers to agricultural systems in which perennial crops are a central strategy for producing farm products and ecosystem services. ● Perennial agriculture offers a range of ecosystem services, including improved soil health and biodiversity, high carbon sequestration rates, agroecosystems better adapted to climate change, improved water quality, and economically viable products. ● Shifting U.S. agriculture to be perennial-focused will require a range of support structures, including federal policy changes. ● Federal policymakers should support perennial agriculture by establishing safety nets like those available for annual crops, centering perennial practices in cost-sharing conservation programs, facilitating market opportunities, and investing in perennial agriculture research and development.